2021
DOI: 10.3390/cells10040855
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Antibody Protects Brain from Neuropathology of Hypoperfusion

Abstract: Chronic brain hypoperfusion is the primary cause of vascular dementia and has been implicated in the development of white matter disease and lacunar infarcts. Cerebral hypoperfusion leads to a chronic state of brain inflammation with immune cell activation and production of pro-inflammatory cytokines, including IL-1β. In the present study, we induced chronic, progressive brain hypoperfusion in mice using ameroid constrictor, arterial stenosis (ACAS) surgery and tested the efficacy of an IL-1β antibody on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Microglia play a critical role in WMLs and an elevated inflammatory response parallel with WMLs, 59,60 as is shown in our study. Meanwhile, recent studies indicated that pro‐inflammatory activated microglia could exacerbate WMLs 61 and release pro‐inflammatory markers 62,63 . Our research identified a noticeable activation of the hippocampal microglia and enhanced secretion of pro‐inflammatory cytokines in VCI mice, which was reversed by hyperforin treatment.…”
Section: Discussionmentioning
confidence: 53%
“…Microglia play a critical role in WMLs and an elevated inflammatory response parallel with WMLs, 59,60 as is shown in our study. Meanwhile, recent studies indicated that pro‐inflammatory activated microglia could exacerbate WMLs 61 and release pro‐inflammatory markers 62,63 . Our research identified a noticeable activation of the hippocampal microglia and enhanced secretion of pro‐inflammatory cytokines in VCI mice, which was reversed by hyperforin treatment.…”
Section: Discussionmentioning
confidence: 53%
“…Inducible nitric oxide synthase (iNOS), one of the enzymes that produces nitric oxide (NO) from the amino acid l-arginine confers some anti-inflammatory properties that regulate human asthma while IL-1β antibody has some protective effects on the brain from neuropathology of hypoperfusion [29]. An increased phenotypic marker of M1, which are IL-1β and iNOS during RSV infection can cause neurotoxicity and DNA damage respectively [30].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS is one of the enzymes that produces nitric oxide from the amino acid l ‐arginine confers some pro and anti‐inflammatory biomarkers that regulate human asthma while IL‐1β antibody has some protective effects on the brain from neuropathology of hypoperfusion 23 . An increased phenotypic marker of M1, which are IL‐1β and iNOS during RSV infection can cause neurotoxicity and DNA damage respectively 24 . Microglia affects the immune microenvironment of neurons mainly through the release of effector factors from different phenotypes after activation, thus affecting neuronal survival 25 .…”
Section: Discussionmentioning
confidence: 99%
“…23 An increased phenotypic marker of M1, which are IL-1β and iNOS during RSV infection can cause neurotoxicity and DNA damage respectively. 24 Microglia affects the immune microenvironment of neurons mainly through the release of effector factors from different phenotypes after activation, thus affecting neuronal survival. 25 Due to the further expression of biomarkers in our study, when Ampicillin is added, Butyrivibrio decreased significantly.…”
Section: Rsv Infection Induced Pulmonary Dysbacteriosismentioning
confidence: 99%